Preparation of Eumelanin-Encapsulated Stereocomplex Polylactide Nano/Microparticles for Degradable Biocompatible UV-Shielding Products - Oceu Dwi Putri; Atitsa Petchsuk; Suthawan Buchatip; Wilairat Supmak; Chariya Kaewsaneha; Kamonchanok Thananukul; Bunthoeun Nim; Sinan Bayram; Kanjana Thumanu; Pakorn Opaprakasit (Nanomaterials and Nanotechnology)
The role of eumelanin as a natural pigment in protecting human skin from ultraviolet (UV) light has drawn vast interest in the research and industrial community. Encapsulation of the compound by various shell materials has been extensively studied to optimize and prolong its shielding efficiency from UV penetration through the skin. Polylactide (PLA)-based copolymers have been widely used in the encapsulation of various active compounds due to their biocompatibility and biodegradability that facilitate sustained release of the active compounds. In this work, stereocomplex PLA (sc-PLA) derived from mixtures of poly(D-lactide-caprolactone-D-lactide), P(DLA-b-CL-b-DLA), a triblock copolymer with linear poly(L-lactide), and PLLA are employed to encapsulate eumelanin by an oil-in-water emulsion (O/W) technique. The effect of eumelanin distribution in PLA’s enantiomers and ultrasonication on the physicochemical properties, encapsulation efficiency, and release behavior of the nano/microparticles were evaluated. The potential application of the resulting particles for sunscreen products was assessed in terms of UV absorbance and in vitro sun protection factor (SPF). The nano/microparticles show a hollow spherical structure, whose size can be controlled by ultrasonication. The distribution of eumelanin and the ultrasonication process play a key role in the growth of sc-PLA and the crystalline structure of the particles. The highest encapsulation efficiency of 46.6% was achieved for sc-PLA2U particles. The high content of eumelanin and the hollow structure with a large surface area lead to improvement in the UV absorbance and sunscreen performance of the particles, as revealed by the increase in the SPF value from 9.7 to 16.5. The materials show high potential for various applications, especially in cosmetic and pharmaceutical fields, as UV-shielding products.